Mechanistic Study of Oil Adsorption Behavior and CO2 Displacement Mechanism Under Different pH Conditions - Xinwang Song; Yang Guo; Yanchang Chen; Shiling Yuan (Molecules)
Enhanced oil recovery (EOR) via CO2 flooding is a promising strategy for improving hydrocarbon recovery and carbon sequestration, yet the influence of pH on solid–liquid interfacial interactions in quartz-dominated reservoirs remains poorly understood. This study employs molecular dynamics (MD) simulations to investigate the pH-dependent adsorption behavior of crude oil components on quartz surfaces and its impact on CO2 displacement mechanisms. Three quartz surface models with varying ionization degrees (0%, 9%, 18%, corresponding to pH 2–4, 5–7, and 7–9) were constructed to simulate different pH environments. The MD results reveal that aromatic hydrocarbons exhibit significantly stronger adsorption on quartz surfaces at high pH, with their maximum adsorption peak increasing from 398 kg/m3 (pH 2–4) to 778 kg/m3 (pH 7–9), while their alkane adsorption peaks decrease from 764 kg/m3 to 460 kg/m3. This pH-dependent behavior is attributed to enhanced cation–π interactions that are facilitated by Na+ ion aggregation on negatively charged quartz surfaces at high pH, which form stable tetrahedral configurations with aromatic molecules and surface oxygen ions. During CO2 displacement, an adsorption–stripping–displacement mechanism was observed: CO2 first forms an adsorption layer on the quartz surface, then penetrates the oil phase to induce the detachment of crude oil components, which are subsequently displaced by pressure. Although high pH enhances the Na+-mediated weakening of oil-surface interactions, which leads to a 37% higher diffusion coefficient (8.5 × 10−5 cm2/s vs. 6.2 × 10−5 cm2/s at low pH), the tighter packing of aromatic molecules at high pH slows down the displacement rate. This study provides molecular-level insights into pH-regulated adsorption and CO2 displacement processes, highlighting the critical role of the surface charge and cation–π interactions in optimizing CO2-EOR strategies for quartz-rich reservoirs.